A PLA copolymer polycarbonate biaxially oriented film and a method for preparing the same
Patent Information
- Application Number
- CN202611062417.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-08-28
AI Technical Summary
例如,CN104693709B通过两步共混结合端基改性剂提升PLA/PC体系的加工热稳定性,但该共混材料在80℃以上环境下拉伸强度保持率不足60%,耐温性能仍不理想
[0024] This invention sets the longitudinal stretching preheating temperature based on the material's specific Tg, ensuring uniform softening of the thick sheet and facilitating molecular chain orientation. The lower stretching rate allows for more time for molecular chains to relax and align, reducing internal stress and defects. A slightly higher transverse stretching temperature compensates for the lower heating efficiency of the tenter frame, ensuring consistent temperature between the sheet's center and surface, thus achieving uniform stretching. A two-stage heat setting process is employed: first, high temperature rapidly releases most of the tensile stress, then the structure is stabilized at a slightly lower temperature, with a total time of at least 15 seconds. This effectively fixes the orientation structure, significantly reducing the film's thermal shrinkage rate and ensuring dimensional stability during subsequent processing and use.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials technology, specifically relating to a PLA copolycarbonate biaxially oriented film with high heat resistance and high light transmittance and its preparation method. Background Technology
[0002] Polylactic acid (PLA), as a biodegradable and green polymer material, has broad application prospects in packaging, textiles, and disposable products. However, PLA itself has drawbacks such as poor heat resistance (low glass transition temperature), high brittleness, and insufficient melt strength, which limit its application in high-end film materials (such as optical films and high-barrier packaging films). To improve the performance of PLA, existing technologies typically employ blending or copolymerization with polycarbonate (PC). For example, CN104693709B improves the processing thermal stability of the PLA / PC system through a two-step blending process combined with end-group modifiers, but the tensile strength retention rate of this blend is less than 60% at temperatures above 80°C, and its temperature resistance is still unsatisfactory. CN116535625A uses a copolymerization strategy of PLA and carbon dioxide-based polycarbonate (PPC), which improves environmental friendliness, but its linear molecular chain structure results in low melt strength (<5cN), and poor component compatibility leads to a light transmittance of less than 75%, making it difficult to meet the requirements of optical-grade films.
[0003] Furthermore, when PLA-based materials are used to prepare thin films via biaxial stretching, traditional linear polymers are prone to high film breakage rates and poor thickness uniformity due to uneven molecular chain orientation and insufficient melt strength. Simultaneously, PLA and PC are susceptible to hydrolysis and thermal oxidative degradation under high-temperature processing conditions, further affecting the mechanical and optical properties of the thin films. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a PLA copolymer polycarbonate biaxially oriented film with high temperature resistance, high light transmittance, excellent melt strength and hydrolytic stability, and a method for preparing the same.
[0005] The technical solution adopted by the present invention to solve its technical problem is: a PLA copolymer polycarbonate biaxially oriented film, characterized in that it is prepared by melt extrusion, biaxial stretching and heat setting of raw materials comprising the following parts by weight: 100 parts of PLA copolymer polycarbonate (PPCL) with a weight average molecular weight of 80000g / mol to 600000g / mol and 1 to 20 parts of additives.
[0006] Preferably, the PLA copolymer polycarbonate has the structural formula A. n-C, where A is the PLA copolymer polycarbonate chain, n is an integer from 3 to 20, and C is a multi-arm macromolecular initiator residue; 0.3 to 0.6 parts by weight of chain extender; 0.5 to 1.0 parts by weight of anti-hydrolysis agent; 0.1 to 0.2 parts by weight of lubricant; 0.1 to 0.3 parts by weight of primary antioxidant and 0.2 to 0.4 parts by weight of secondary antioxidant.
[0007] The formulation system of this invention uses PLA copolymer polycarbonate with a specific multi-arm topology as the matrix. Its star-shaped network can form effective physical cross-linking points during melt stretching, significantly improving the stretching ratio and fundamentally reducing the risk of film breakage during high-speed stretching. The synergistic effect of chain extenders and anti-hydrolysis agents can instantly repair molecular chain breakage caused by trace amounts of moisture or thermomechanical stress under high-temperature and high-shear processing conditions, and endow the product with excellent long-term anti-hydrolytic aging properties, ensuring the lifespan of the film under harsh usage conditions. The combination of primary and secondary antioxidants effectively inhibits thermo-oxidative degradation during processing, prevents material yellowing, and ensures optical stability. The addition of lubricants effectively improves the surface properties of the film, prevents winding adhesion, and provides convenience for subsequent secondary processing such as printing and lamination.
[0008] Preferably, the weight-average molecular weight of the PLA copolymer polycarbonate is 80,000 g / mol to 600,000 g / mol.
[0009] Preferably, the PLA copolymer polycarbonate or PLA copolymer polycarbonate chain is copolymerized from an epoxy compound, carbon dioxide, polylactic acid, and optionally a cyclic anhydride; the polylactic acid has a weight-average molecular weight of 2000 g / mol to 300000 g / mol and a molecular weight distribution index of 1.9 to 2.5. Using PLA with a wide molecular weight distribution in the copolymerization process allows low-molecular-weight PLA segments to preferentially react and form copolymerization seeds, accelerating the process, while high-molecular-weight PLA segments are slowly inserted after partial chain breakage during copolymerization, ultimately forming randomly distributed PLA blocks on the molecular chain. This structure effectively disrupts the regularity of the polycarbonate chain, thereby obtaining a highly transparent amorphous structure. Simultaneously, the chain length differences resulting from the wide distribution enhance the entanglement between molecular chains, which is beneficial for the uniform transmission of tensile stress and improves the mechanical balance of the film.
[0010] Preferably, the epoxy compound is a mixture of ethylene oxide and C3-C20 epoxides, wherein the molar percentage of ethylene oxide is 60%-70%; the C3-C20 epoxides are selected from at least one of propylene oxide, 1,2-epoxide butane, and cyclohexane oxide. By limiting the specific proportion of ethylene oxide in the epoxy compound mixture, the ratio of the flexible segments of homopolymerized ethylene oxide to the rigid segments of copolymerized long-chain epoxides can be precisely controlled within the molecular chain. This design allows the material to maintain sufficient rigidity and temperature resistance while introducing appropriate flexibility, effectively alleviating internal stress and reducing film brittleness. Furthermore, this copolymer structure helps reduce the overall crystallization tendency and light scattering, which is one of the key factors in achieving high transmittance and low haze.
[0011] Preferably, the chain extender is an oxazoline compound or an epoxy-functionalized acrylate polymer; and / or, the anti-hydrolysis agent is a carbodiimide compound. Choosing oxazoline or epoxy-functionalized polymers as chain extenders allows their active groups to react efficiently with the carboxyl or hydroxyl groups at the polymer chain ends, dynamically connecting broken molecular chains during processing, effectively restoring and increasing molecular weight, thereby significantly enhancing melt strength and giving the film better dimensional stability and a lower breakage rate during longitudinal (MD) and transverse (TD) stretching. Simultaneously, the use of carbodiimide anti-hydrolysis agents preferentially reacts with ester bonds or potentially intruding water molecules in the material to form a stable structure, chemically blocking the hydrolysis chain reaction and greatly improving the long-term durability of the film in humid environments.
[0012] Preferably, the raw material further includes 0.05 to 0.15 parts by weight of a nucleating agent, wherein the nucleating agent is a sorbitol derivative. Adding a specific amount of sorbitol-based nucleating agent can induce the formation of a large number of tiny and uniform crystal nuclei during biaxial stretching. These microcrystals are much smaller than the wavelength of visible light, therefore they do not have a significant negative impact on light transmittance. Instead, they act as physical crosslinking points, restricting the movement of molecular chains, thereby further improving the rigidity, heat resistance (heat distortion temperature), and dimensional stability of the film without sacrificing transparency. This makes it particularly suitable for industrial applications requiring high flatness and temperature resistance.
[0013] Preferably, the raw materials further include 0.1-0.3 parts by weight of a light-reflecting agent and 0.5-1.0 parts by weight of an antistatic agent. The light-reflecting agent is silicone or acrylate nanoparticles, and the antistatic agent is a permanent polymeric antistatic agent. The addition of light-reflecting and antistatic agents is an optimization of this invention for optical film applications. Nanoscale silicone or acrylate light-reflecting agents can effectively fill microscopic defects in the polymer matrix, and their refractive index is designed to match the matrix, thereby minimizing interfacial light scattering, reducing haze to a lower level, and achieving ultra-high-definition light transmission. The permanent polymeric antistatic agent forms charge dissipation channels through its hydrophilic segments in the matrix, providing durable antistatic functionality that is not significantly affected by environmental humidity. This effectively prevents the film from contaminating the surface due to electrostatic adsorption of dust during production and use, which is crucial for the cleanliness of optical components such as display screen protective films and polarizer base films.
[0014] Preferably, the raw materials further include 10-20 parts by weight of a high-barrier polyester or ethylene-vinyl alcohol copolymer, and 2-5 parts by weight of layered silicate nanosheets. This invention introduces a high-barrier polyester (such as PEN) or EVOH to further enhance the barrier properties of the film against gases such as oxygen and water vapor. During biaxial stretching, the layered silicate nanosheets (such as montmorillonite) align highly along the film plane, forming a tortuous "maze" path for gas molecule penetration, greatly extending the penetration time and creating a synergistic effect with the high-barrier polymer, thus multiplying the barrier performance. Although inorganic nanoparticles are added, the overall transparency of the film is controllable due to the nanoscale and the good dispersion formed after stretching and orientation, thereby achieving a good combination of high barrier properties and high transparency.
[0015] Preferably, the raw materials are formulated in the following weight proportions: 100 parts PLA copolymer polycarbonate, 0.3-0.6 parts chain extender, 0.5-1.0 parts anti-hydrolysis agent, 0.1-0.2 parts lubricant, 0.1-0.3 parts primary antioxidant, 0.2-0.4 parts secondary antioxidant, 0.05-0.15 parts nucleating agent, 0.1-0.3 parts penetration enhancer, 0.5-1.0 parts antistatic agent, 10-20 parts high-barrier polyester or ethylene-vinyl alcohol copolymer, and 2-5 parts layered silicate nanosheets.
[0016] This comprehensive formulation achieves a performance breakthrough through the synergistic effect of multiple components. A specific ratio of chain extenders and anti-hydrolysis agents dynamically repairs molecular chains and blocks hydrolysis pathways during processing. Nucleating agents and antireflective agents synergistically regulate the crystal structure, enhancing rigidity while ensuring high light transmittance. An antistatic agent provides durable dustproof functionality. High-barrier resin and nanosheets, after biaxial stretching, form a multi-layered barrier network, enabling the film to maintain excellent barrier properties while retaining low haze. The precise proportions of each component result in a glass transition temperature of 56℃~62℃, light transmittance ≥90%, haze ≤5%, and tensile strength retention ≥80% at 80℃. The glass transition temperature of this invention is significantly higher than that of ordinary PLA films, meaning the film can maintain shape and performance stability at higher temperatures. The excellent light transmittance and haze ensure superior optical quality, meeting the requirements of high-end optical and packaging applications. Most importantly, the tensile strength retention rate is ≥80% at 80℃, which proves that the film of the present invention has excellent heat resistance and structural stability, far superior to traditional PLA / PC blend materials, enabling it to be applied in scenarios requiring high-temperature use.
[0017] A method for preparing the above-mentioned PLA copolymer polycarbonate biaxially oriented film includes the following steps:
[0018] (1) Raw material pretreatment: Dry each component raw material at 80℃~100℃ and dew point below -40℃ for at least 6 hours to make the water content below 200 ppm;
[0019] (2) Extrusion casting: The dried raw material is melted and blended, and then extruded and cast onto the cooling roller through a die to form an amorphous thick sheet. The extrusion temperature is 175℃~215℃ and the cooling roller temperature is 40℃~60℃.
[0020] (3) Biaxial stretching: The thick sheet is first stretched longitudinally and then stretched laterally;
[0021] (4) Heat setting and winding: The stretched film is heat set, then cooled and wound up to obtain the biaxially oriented film.
[0022] Low-temperature vacuum drying thoroughly removes moisture, preventing hydrolytic degradation of PLA and polycarbonate chains during high-temperature processing and ensuring molecular weight stability. The extrusion casting temperature profile ensures full plasticization and prevents degradation of the material. Combined with appropriate cooling roller temperatures, this yields high-quality cast sheets that are amorphous, stress-free, and of uniform thickness—the foundation for successful biaxial stretching. The longitudinal-to-transverse stretching sequence, along with subsequent heat setting steps, ensures full molecular chain orientation and stress relaxation, ultimately resulting in film products with stable performance and precise dimensions.
[0023] Preferably, in step (3), the preheating temperature for longitudinal stretching is the glass transition temperature Tg+5℃~Tg+15℃ of the PLA copolymer polycarbonate, the stretching ratio is 2.8~3.3, and the stretching rate is 100% / s~200% / s; the preheating temperature for transverse stretching is 5℃~10℃ higher than the longitudinal stretching temperature, and the stretching ratio is 3.2~3.8; the heat setting in step (4) is divided into two stages, the temperature of the first stage is 95℃~110℃, the temperature of the second stage is 85℃~100℃, and the total heat setting time is not less than 15s.
[0024] This invention sets the longitudinal stretching preheating temperature based on the material's specific Tg, ensuring uniform softening of the thick sheet and facilitating molecular chain orientation. The lower stretching rate allows for more time for molecular chains to relax and align, reducing internal stress and defects. A slightly higher transverse stretching temperature compensates for the lower heating efficiency of the tenter frame, ensuring consistent temperature between the sheet's center and surface, thus achieving uniform stretching. A two-stage heat setting process is employed: first, high temperature rapidly releases most of the tensile stress, then the structure is stabilized at a slightly lower temperature, with a total time of at least 15 seconds. This effectively fixes the orientation structure, significantly reducing the film's thermal shrinkage rate and ensuring dimensional stability during subsequent processing and use.
[0025] Compared with existing technologies, this invention has the following advantages: Through unique molecular structure design, innovative additive formulation system, and refined biaxial stretching process, this invention successfully prepares a PLA copolymer polycarbonate biaxially oriented film with excellent comprehensive performance. This film achieves a balance of high heat resistance, high light transmittance, low haze, high tensile strength retention, and good processing stability, breaking through the performance bottleneck of traditional PLA-based materials in high-end film applications. It provides a new solution for the widespread application of green polymer materials in optics, high-barrier packaging, and industrial fields. Detailed Implementation
[0026] The present invention will be further described below with reference to embodiments, but these are not intended to limit the scope of the invention. Unless otherwise specified, all raw materials used in the following embodiments are commercially available. The PLA copolymer polycarbonate was prepared in-house, with a number-average molecular weight of approximately 45,000 g / mol and a glass transition temperature of approximately 58°C. The testing methods are as follows: the glass transition temperature was determined using the DSC method (heating rate 10°C / min); light transmittance and haze were determined according to ASTM D1003 standard; tensile strength and retention were determined according to ASTM D882 standard. Process conditions not explicitly stated in other embodiments are as described in Example 1.
[0027] Example 1
[0028] 100 parts by weight of PLA copolymer polycarbonate, 0.45 parts by weight of epoxy-functionalized acrylate polymer chain extender Joncryl® ADR-4370S, 0.75 parts by weight of carbodiimide anti-hydrolysis agent Stabaxol® P, 0.15 parts by weight of erucamide lubricant, 0.2 parts by weight of hindered phenolic primary antioxidant Irganox® 1010, and 0.3 parts by weight of phosphite secondary antioxidant Irgafos® 168 were premixed uniformly in a high-speed mixer. The mixture was dried in a dehumidifying dryer at 85°C and a dew point of -50°C for 6 hours, and the moisture content was measured to be 150 ppm. Subsequently, the dried material was fed into a twin-screw extruder and melt-blended at temperatures set as follows: Zone 1 175℃, Zone 2 185℃, Zone 3 195℃, Zone 4 205℃, melt pump 210℃, and die 210℃. The resulting material was extruded through a T-die onto a cooling roller with a surface temperature of 45℃, forming an amorphous sheet approximately 200μm thick. This sheet was first longitudinally stretched at a preheating temperature of 68℃, a stretch ratio of 3.0, and a stretching rate of approximately 150% / s. Then, it underwent transverse stretching at a preheating temperature of 73℃ and a stretch ratio of 3.5. Finally, the biaxially stretched film underwent a first stage of heat setting at 100℃, followed by a second stage at 90℃, for a total heat setting time of approximately 20s. After cooling, the film was wound up to obtain a biaxially stretched film approximately 20μm thick.
[0029] Tests showed that the film has a glass transition temperature of 59°C, a light transmittance of 92.5%, a haze of 3.2%, and a tensile strength retention rate of 85% at 80°C.
[0030] Example 2
[0031] Based on the basic formulation of Example 1, 0.2 parts by weight of an organosilicon nano-reflective agent and 0.75 parts by weight of a polyether-esteramide type permanent antistatic agent were added. Simultaneously, PLA copolymer polycarbonate raw materials were rigorously screened to achieve a molecular weight distribution index of 1.5. All additives were added in the form of high-concentration masterbatch. The preparation process was the same as in Example 1, but the cooling roller temperature was precisely controlled at 40°C to ensure optimal mirror finish and minimal haze.
[0032] The resulting film exhibits extremely high surface gloss. Test results show that the light transmittance is increased to 94.0%, the haze is significantly reduced to 1.8%, and it also possesses a long-lasting antistatic effect with a surface resistivity of 10. 10 On the order of Ω / sq.
[0033] Example 3
[0034] Based on the formulation of Example 1, 15 parts by weight of polyethylene naphthalate was added as a high-barrier polyester, and 3.5 parts by weight of organo-modified montmorillonite nanosheets were added. Simultaneously, the amount of chain extender was increased to 0.6 parts by weight, and 1 part by weight of maleic anhydride graft compatibilizer was added. In the extrusion casting process, the melt temperature was increased to 215°C to ensure sufficient plasticization of the polyethylene naphthalate. The biaxial stretching process parameters were basically the same as in Example 1.
[0035] Tests showed that the oxygen permeability of the obtained film was less than 5 cm. 3 / (m 2 (day·atm), water vapor transmission rate is less than 2g / (m 2 (day), while the light transmittance remains at 89.5% and the haze is 4.5%.
[0036] Example 4
[0037] The formulation of Example 1 was used, except that the longitudinal stretch ratio was set to 2.8, and a two-stage heat setting process of 100℃+90℃ was employed. Its heat shrinkage rate at 80℃ for 30 minutes remained stable below 1.5%.
[0038] Example 5
[0039] The formulation of Example 1 was used, except that the longitudinal stretch ratio was set to 3.3 and a two-stage heat setting at 100℃+90℃ was adopted.
[0040] Example 6
[0041] The formulation of Example 1 was specifically adjusted: the amount of nucleating agent sorbitol derivative Millad® NX 8000 was increased to 0.15 parts by weight, and an additional 0.8 parts by weight of ultrafine precipitated barium sulfate powder was added as a rigid filler. The preheating temperature for longitudinal stretching was set to 63°C, with a higher stretching ratio of 3.3; the preheating temperature for transverse stretching was 70°C, with a stretching ratio of 3.8. Higher temperature settings were used in the heat setting stage, with the first stage at 110°C and the second stage at 100°C, and the total time was extended to 25 seconds.
[0042] The resulting film exhibits an elastic modulus (ASTM D882) that is approximately 40% higher than that of the film in Example 1, demonstrating extremely high rigidity. Furthermore, its heat shrinkage rate (120°C, 30 min) is less than 1.0%, indicating excellent dimensional stability.
[0043] Example 7
[0044] PLA copolymer polycarbonate was prepared using broad-distribution PLA with a weight-average molecular weight of 50,000 g / mol and a molecular weight distribution index of 2.4. The formulation and other process conditions were exactly the same as in Example 1.
[0045] During the biaxial stretching process, a breakage rate of approximately 15% was observed compared to the control experiment using narrow-distribution PLA, indicating better processing stability. Performance testing of the final film revealed that the ratio of its longitudinal (MD) to transverse (TD) tensile strength was closer to 1 (approximately 1.1:1), indicating more balanced film performance.
[0046] Example 8
[0047] Using the formulation of Example 1, the specific operation is as follows: the drying time is strictly controlled at 6 hours, the longitudinal stretching rate is set at a high level of 200% / s, and the total heat setting time is precisely controlled at 15 seconds. The longitudinal stretching preheating temperature is set at 63°C, and the stretching ratio is 2.8; the transverse stretching preheating temperature is set at 68°C, and the stretching ratio is 3.2.
[0048] Example 9
[0049] Based on the formula of Example 1, the drying conditions were set to 90°C for 7 hours to ensure that the moisture content remained stable below 100 ppm, providing a more adequate stability guarantee for subsequent high-temperature processing. Longitudinal stretching: The preheating temperature was set to 65°C, a medium stretching ratio of 3.1 was selected, and a medium stretching rate of 150% / s was used. Transverse stretching: The preheating temperature was set to 70°C, and the stretching ratio was set to 3.6. Enhanced heat setting process: The first stage heat setting temperature was 108°C, the second stage was 98°C, and the total heat setting time was extended to 22 seconds.
[0050] Comparative Example 1
[0051] The same PLA copolymer polycarbonate matrix as in Example 1 was used, but no chain extender and anti-hydrolysis agent were added, and other process parameters remained unchanged.
[0052] During the extrusion casting process, the melt pressure fluctuated significantly, indicating severe degradation. The resulting film was slightly yellowish in color, and its intrinsic viscosity decreased by approximately 20% compared to the sample in Example 1. After aging in a constant temperature and humidity chamber at 85°C and 85% relative humidity for 168 hours, the film showed significant embrittlement, with a mechanical property loss exceeding 50%, while the film in Example 1 maintained over 90% of its properties under the same conditions.
[0053] Comparative Example 2
[0054] Based on the formulation of Example 1, the amount of epoxy-functionalized acrylate polymer chain extender added was increased to 1.0 parts by weight, while other conditions remained unchanged.
[0055] During melt extrusion, an abnormal increase in melt viscosity and increased die pressure fluctuations were observed, along with a slight sharkskin-like appearance on the extrudate surface, indicating a risk of excessive crosslinking or gelation. Although film formation was achieved, the film felt noticeably harder and more brittle, with a significantly reduced elongation at break to less than 20%, far below the 50% or more of the film in Example 1. Simultaneously, the film's transmittance decreased to 88%, and its haze increased to 6.5%. This suggests that excessive chain extender leads to excessive inter-chain bonding, which in turn impairs the material's processability and the final film's toughness and optical properties.
[0056] Comparative Example 3
[0057] The cast thick sheet was successfully prepared using the formulation of Example 1 and subjected to biaxial stretching. However, in the final heat setting stage, it was only treated at 90°C for 5 seconds, which is lower than the process conditions of two heat setting stages and a total time of not less than 15 seconds required by the present invention.
[0058] The initial optical and mechanical properties of the newly produced film were not significantly different from those of Example 1. However, after suspending the film freely in an oven at 100°C for 10 minutes, both its longitudinal and transverse thermal shrinkage rates exceeded 8%, indicating severe dimensional shrinkage. In contrast, the thermal shrinkage rate of the film in Example 1 remained stable at less than 2% under the same conditions.
[0059] To systematically evaluate the performance of the PLA copolycarbonate biaxially oriented film described in this invention, the film samples prepared in the above embodiments and comparative examples were subjected to unified testing. The testing standards and methods are as follows:
[0060] Glass transition temperature (Tg): Differential scanning calorimetry (DSC) was used with a heating rate of 10°C / min.
[0061] Transmittance and haze: measured according to ASTM D1003 standard.
[0062] Tensile strength and retention rate: The tensile strength of the film at room temperature (23℃) was determined according to ASTM D882 standard, and its tensile strength at that temperature was tested immediately after pretreatment in an 80℃ constant temperature oven for 30 min, and the retention rate was calculated.
[0063] Heat shrinkage rate: Cut a film sample of a certain size, hang it freely in an oven at 100℃ for 10 minutes, and measure the dimensional change after cooling. Calculate the longitudinal (MD) and transverse (TD) heat shrinkage rates.
[0064] Oxygen Transmission Rate (OTR): Measured according to ASTM D3985 standard.
[0065] Water vapor transmission rate (WVTR): Measured according to ASTM F1249 standard.
[0066] Surface resistivity: Measured according to ASTM D257 standard.
[0067] The detailed performance test results of each embodiment and comparative example are summarized in Table 1 below.
[0068] Table 1 Performance test results of the examples and comparative examples
[0069] .
[0070] The embodiments and comparative examples of this invention have been specifically designed and adjusted in terms of basic formulation and process. Example 1 serves as a basic reference, demonstrating the balanced performance of the core formulation. Example 2, by using narrow molecular weight distribution PLA and adding nano-reflective agents and antistatic agents, focuses on optimizing optical and antistatic properties. Example 3 aims to achieve better barrier properties by introducing high-barrier polyester (PEN) and layered nanosheets. Examples 4 and 5 respectively show the effects of lower and higher longitudinal stretch ratios on film properties, while Example 6, by adding nucleating agents and rigid fillers, focuses on improving the rigidity and dimensional stability of the film. Example 7 uses wide molecular weight distribution PLA for copolymerization, verifying its effect on improving processing stability and mechanical balance. Examples 8 and 9 respectively investigate the shaping effects of high-speed stretching process and enhanced drying and heat setting process on film properties. In contrast, Comparative Example 1, by omitting key chain extenders and anti-hydrolysis agents, revealed their decisive role in processing stability and long-term durability; Comparative Example 2, through the excessive use of chain extenders, demonstrated the damage that improper formulation can cause to material toughness and optical properties; and Comparative Example 3, by significantly shortening the heat setting time, confirmed the irreplaceable importance of thorough heat setting for achieving low heat shrinkage and dimensional stability. These systematic comparisons fully validate the rationality and superiority of the formulation and process design of this invention.
[0071] The test results of Comparative Example 1 show the crucial role of chain extenders and anti-hydrolysis agents in processing stability and long-term durability. The test results of Comparative Example 2 show that exceeding the limits of this invention with chain extender dosage leads to excessive crosslinking, impairing the toughness and optical properties of the film. The test results of Comparative Example 3 show the decisive role of the heat setting process in achieving low heat shrinkage and dimensional stability. Its initial optical and mechanical properties are similar to those of Example 1, but its heat shrinkage rate far exceeds the acceptable standard.
[0072] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any other way. Any person skilled in the art may make changes or modifications to the above-disclosed technical content to create equivalent embodiments. However, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the protection scope of the present invention.
Claims
1. A PLA copolymer polycarbonate biaxially oriented film, characterized in that, It is prepared by melt extrusion, biaxial stretching and heat setting of raw materials including the following parts by weight: 100 parts of PLA copolymer polycarbonate and 1-20 parts of additives.
2. The PLA copolycarbonate biaxially oriented film according to claim 1, characterized in that, The PLA copolymer polycarbonate chain A is copolymerized from epoxy compound, carbon dioxide, polylactic acid and optional cyclic anhydride; the polylactic acid has a weight-average molecular weight of 2000 g / mol to 300000 g / mol and a molecular weight distribution index of 1.9 to 2.
5.
3. The PLA copolycarbonate biaxially oriented film according to claim 2, characterized in that, The epoxy compound is a mixture of ethylene oxide and C3-C20 epoxy alkanes, wherein the molar percentage of ethylene oxide is 60%-70%; the C3-C20 epoxy alkanes are selected from at least one of propylene oxide, 1,2-epoxybutane, and cyclohexane oxide.
4. The PLA copolycarbonate biaxially oriented film according to claim 1, characterized in that, The additives include 0.3 to 0.6 parts by weight of a chain extender, which is an oxazoline compound or an epoxy-functionalized acrylate polymer; and / or, the anti-hydrolysis agent is a carbodiimide compound.
5. The PLA copolycarbonate biaxially oriented film according to claim 1, characterized in that, The adjuvant includes 0.05 to 0.15 parts by weight of a nucleating agent, wherein the nucleating agent is a sorbitol derivative.
6. The PLA copolycarbonate biaxially oriented film according to claim 1, characterized in that, The additives include 0.1 to 0.3 parts by weight of a penetration enhancer and 0.5 to 1.0 parts by weight of an antistatic agent. The penetration enhancer is an organosilicon or acrylate nanoparticle, and the antistatic agent is a permanent polymeric antistatic agent.
7. The PLA copolycarbonate biaxially oriented film according to claim 1, characterized in that, The raw materials also include 10-20 parts by weight of high-barrier polyester or ethylene-vinyl alcohol copolymer, and 2-5 parts by weight of layered silicate nanosheets.
8. The PLA copolycarbonate biaxially oriented film according to claim 1, characterized in that, The raw materials are formulated in the following weight proportions: 100 parts PLA copolymer polycarbonate, 0.3-0.6 parts chain extender, 0.5-1.0 parts anti-hydrolysis agent, 0.1-0.2 parts lubricant, 0.1-0.3 parts primary antioxidant, 0.2-0.4 parts secondary antioxidant, 0.05-0.15 parts nucleating agent, 0.1-0.3 parts penetration enhancer, 0.5-1.0 parts antistatic agent, 10-20 parts high-barrier polyester or ethylene-vinyl alcohol copolymer, and 2-5 parts layered silicate nanosheets.
9. A method for preparing a PLA copolycarbonate biaxially oriented film according to any one of claims 1 to 8, characterized in that, Includes the following steps: (1) Raw material pretreatment: Dry each component raw material at 80℃~100℃ and dew point below -40℃ for at least 6 hours to make the water content below 200ppm; (2) Extrusion casting: The dried raw material is melted and blended, and then extruded and cast onto the cooling roller through a die to form an amorphous thick sheet. The extrusion temperature is 175℃~215℃ and the cooling roller temperature is 40℃~60℃. (3) Biaxial stretching: The thick sheet is first stretched longitudinally and then stretched laterally; (4) Heat setting and winding: The stretched film is heat set, then cooled and wound up to obtain the biaxially oriented film.
10. The method for preparing a PLA copolymer polycarbonate biaxially oriented film according to claim 9, characterized in that, The preheating temperature for longitudinal stretching in step (3) is the glass transition temperature Tg+5℃~Tg+15℃ of the PLA copolymer polycarbonate, the stretching ratio is 2.8~3.3, and the stretching rate is 100% / s~200% / s; the preheating temperature for transverse stretching is 5℃~10℃ higher than the longitudinal stretching temperature, and the stretching ratio is 3.2~3.
8. The heat setting in step (4) is divided into two stages. The temperature of the first stage is 95℃~110℃, and the temperature of the second stage is 85℃~100℃. The total heat setting time is not less than 15s.
Citation Information
Patent Citations
A polylactic acid / polycarbonate alloy material for 3D printing and its preparation method
CN104693709B
Carbon dioxide-based polyester-polycarbonate biodegradable copolymer and preparation method thereof
CN116535625A